Modelo de tomada de decisão para seleção de sistema construtivo para habitação de interesse social - Félix, Francisco Régis Ribeiro (2017)
In the Civil Construction during the planning of the buildings it is necessary to decide which type of construction system to be used in the execution of the work, in view of the desire to achieve a good technical and economic performance in the project. Civil Construction needs modernization in its management processes in order to face the technical and economic challenges imposed on them by the current political and economic context of the country. Customers require products that are quality, affordable and meet their needs. The search for more efficient methodologies to support decision making is the object of this study, so that it can overcome the lack of systematized tools and methods that aid in the decision process. The main objective of this study is to propose a support model for the decision-making to hierarchize the construction systems for Social Interest Housing (HIS). The methodological procedure used consists of interviews with those involved in the decision-making process and the bibliographical survey, through consultations with articles, periodicals, theses, dissertations and books. The research is developed in three stages: definition of the decision context, structuring of the multicriteria model and application of the model. The PROMETHEE II multicriteria method is used in decision support. The result of the application of the model depends directly on the information and preferences of the decision maker. As a conclusion of the application of the model, a hierarchy of the constructive systems considered was obtained, with the following ordering: concrete walls; Steel frame; Structural masonry and traditional masonry. The model contributes to improved decision making